Strategy For The Development of Leading Agriculture Commodities - Khaerunnisa Kherunnisa; Muhammad Wahyu Agung; Banyuriatiga Banyuriatiga; Zulhafandi Zulhafandi; Fitriani R; Ayu Wulandary (Agribusiness Journal, 2023)
The agribusiness potential in the Tana Tidung Regency area has not been managed and utilized optimally. The results obtained are still relatively small and have not been able to empower the community's economy because existing commodities have not been developed into superior commodities. As a result, cross-border or regional trade opportunities have not made a meaningful contribution to society and the region. One alternative in developing the region is to carry out a strategy to develop superior agribusiness commodities so that the region can be developed into a growth center for the surrounding area. The objectives of carrying out this research are (1) to find out the basic and main agricultural sectors. knowing superior agribusiness commodities, (2) to identify the factors that determine the success of developing superior agribusiness commodities, (3) to provide recommendations for strategies for developing superior agribusiness commodities in Tana Tidung Regency. The research results show that the leading commodities in supporting regional development in Tana Tidung Regency based on LQ and B/C ratio values 1 and farmers' preferences are spinach (LQ=8.06), mustard greens (LQ=2.15), kangkong (LQ= 2.18), and cayenne pepper (LQ=1.84). Strategies that can be implemented to develop superior commodities in Tana Tidung Regency are 1) Increasing cooperation/partnerships between farming institutions and the private sector or government, 2) Increasing the supporting capacity of infrastructure, facilities and infrastructure, 3) Optimizing capital assistance from the government as a stimulant for innovation in processing, marketing and socialization of production results, 4) Providing information data to support marketing requests.